Coordinated policy action and flexible coalitional psychology: How evolution made humans so good at politics. (June 2017) - Leech, Beth L.; Cronk, Lee
Abstract: The observation that politics makes strange bedfellows may be hackneyed, but it is also often true: Politicians and other actors in the policy process routinely align themselves on specific issues with actors with whom they otherwise have broad disagreements. This fits with social psychological research showing that humans have a coalitional psychology that is remarkably flexible, allowing us to feel strong bonds toward the coalitions to which we belong but to also break those bonds and move on to new coalitions when circumstances change. How is this flexibility possible? Here we examine the possible ways in which evolutionary forces helped shape our species' trademark flexible coalitional psychology, focusing in particular on gene-culture coevolution and cultural group selection. We conclude with some examples of coordinated policy action among erstwhile foes in contemporary politics.